KINERJA KARYAWAN DI LPD DESA PAKRAMAN PEDUNGAN BERDASARKAN FAKTOR KEMAMPUAN KERJA, FASILITAS DAN MOTIVASI - Setiawati, Ni Kadek Yuli; Parwita, Gde Bayu Surya; Prastyadewi, Made Ika (STKIP PGRI Jombang, 2023)
Employee performance is the result of work or work performance (in terms of quality and quantity) of an individual in carrying out his duties and responsibilities in an organization. The purpose of this study was to determine the effect of work ability, work facilities and motivation on employee performance at LPD Pedungan Village.This research was conducted at the LPD Pedungan Village, which is located on Pulau Belitung Street Number 36 Pedungan – South Denpasar. The object of this research is work ability, work facilities, motivation and employee performance at LPD Pedungan Village. The population in this study were all 35 employees of the LPD Pedungan Village, with the census method used as a sampling method so that all populations were used as samples. The analysis technique used is Multiple Linear Regression Analysis.The results in this study indicate that all independent variables which include work ability, work facilities and motivation have a positive and significant impact on employee performance at LPD Pedungan Village. The results of this analysis can be interpreted that if work ability, work facilities and motivation are improved, it will be followed by an increase in employee performance at LPD Pedungan Village.